Uniportal endoscopic decompression and debridement for infectious diseases of spine with neurological deficits: a retrospective study in China - Hui Lv; Jianhong Zhou; Yuan Guo; Sheng Liao; Hui Chen; Fei Luo; Jianzhong Xu; Zhongrong Zhang; Zehua Zhang (Asian Spine Journal)
Study Design A retrospective study. Purpose To evaluate the clinical efficacy of uniportal endoscopic decompression and debridement (UEDD) in treating infectious diseases of the spine (IDS) with neurological deficits. Overview of Literature IDS patients with neurological deficits often require urgent surgical decompression. However, the efficacy of UEDD in this complex patient population is not well-characterized. Methods This retrospective study analyzed 32 consecutive IDS patients who underwent UEDD surgery. Clinical features, laboratory data (erythrocyte sedimentation rate and C-reactive protein), and treatment outcomes were analyzed. Results Definite microorganisms were identified in 27 patients (84.3%), with 24 (88.9%) meeting cure criteria. The cure rate was significantly higher in the detected pathogen group compared to the undetected pathogen group (88.9% vs. 80%; χ2=19.36, p<0.0001). Metagenomic next generation sequencing (mNGS) provided faster diagnosis (41.72±6.81 hours) compared to tissue culture (95.74±35.47 hours, p<0.05). The predominant causative pathogen was Mycobacterium tuberculosis, followed by Staphylococcus aureus. Significant improvements were observed in Visual Analog Scale pain scores, from a mean of 7.9 preoperatively to 1.06 at 1 year postoperatively. The Oswestry Disability Index revealed a similar trend, showing significant improvement (p<0.05). Conclusions UEDD is a viable alternative to traditional open surgery for managing IDS in high-risk patients. UEDD offers a dual therapeutic-diagnostic advantage during the initial admission phase, enabling simultaneous debridement, neurological decompression, and targeted biopsy in a single intervention. Compared with traditional tissue culture, mNGS enables rapid microbiological diagnosis and extensive pathogen coverage.